UM NOVO INSETO ASSOCIADO AOS VIVEIROS FLORESTAIS: Sciara SP. (DIPTERA: SCIARIDAE) - Berti Filho, Evoneo; Wilcken, Carlos Frederico (REVISTA DE AGRICULTURA, 2015)
UM NOVO INSETO ASSOCIADO AOS VIVEIROS FLORESTAIS: Sciara SP. (DIPTERA: SCIARIDAE)